2018
DOI: 10.2320/matertrans.m2017400
|View full text |Cite
|
Sign up to set email alerts
|

Volatilization of Arsenic and Antimony from Tennantite/Tetrahedrite Ore by a Roasting Process

Abstract: The volatilization of arsenic (As) and antimony (Sb) impurities in a copper ore consisting of tennantite (Cu 12 As 4 S 13)/tetrahedrite (Cu 12 Sb 4 S 13) by roasting in both nitrogen and air atmospheres was investigated in this study. The roasting experiments were performed at different temperatures ranging from 500 to 1200°C and different retention times from 15 to 60 minutes while the nitrogen and air flow to a furnace chamber was same as 300 ml/min. The results showed that at 700°C, the maximum As volatiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…[7][8][9][10] Removal efficiency of As has been found to be much better compared with that of Sb while roasting in inert conditions up to 700 °C. [4,9,11] Haga et al [11] reported that only above 700 °C did the Sb volatilization in inert atmosphere improve appreciably and up to 90 pct removal could be achieved at 1200 °C. However, the problem of incipient sintering of the calcines has been frequently reported [7,9,10] when the temperature of 700 °C is approached while heating the polymetallic concentrates in inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Removal efficiency of As has been found to be much better compared with that of Sb while roasting in inert conditions up to 700 °C. [4,9,11] Haga et al [11] reported that only above 700 °C did the Sb volatilization in inert atmosphere improve appreciably and up to 90 pct removal could be achieved at 1200 °C. However, the problem of incipient sintering of the calcines has been frequently reported [7,9,10] when the temperature of 700 °C is approached while heating the polymetallic concentrates in inert atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5, As removal is shown to be higher than the Sb removal for most of the concentrates, owing to the low volatility of Sb from the sulfosalt minerals. [43] Previous experimental [28,32,53] and model-based theoretical studies [54] have also corroborated a high As volatilization of > 90 pct in inert atmosphere at 700°C from concentrates comprising As minerals such as enargite (Cu 3 AsS 4 ) [32,54] and tennantite (Cu 12 As 4 S 13 ). [28,53] In the current investigation, As content at 700°C was highest in the Maurliden concentrate, which also had the highest initial As content (Table IV).…”
Section: B Sb and As Volatilization During Roasting Experimentsmentioning
confidence: 84%
“…Alternatively, roasting of Cu-concentrates can also partially volatilize the impurity elements As and Sb. [21][22][23][24][25][26][27][28][29][30] Therefore, advancements in the roasting technology can also facilitate the increase in proportions of the complex concentrates in blends processed for pyrometallurgical Cu extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Therefore, the volatilization of these elements from the sulfide concentrates during roasting have been studied in different controlled atmospheric environments. [14][15][16][17][18][19][20][21][22] However, the properties of volatilized and condensed Sb-and As-bearing species emanating from the sulfide concentrates during roasting have been rarely studied. Also, the effect of simultaneous release of volatile species by the other minerals such as pyrite present in the concentrate (comprising of labile sulfur [23] ) on the gas phase complexation behavior of Sb and As has not been investigated.…”
Section: Introductionmentioning
confidence: 99%